2020
DOI: 10.7150/ijbs.38846
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of a novel multi-mRNA signature for predicting relapse of cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is an epithelial cancer and has high death and recurrence rates, current methods cannot satisfy the need for predicting cancer relapse effectively. So, we aimed at conducting a multi-mRNA signature to improve the relapse prediction of CCA. We analyzed mRNA expression profiling in large CCA cohorts from the Gene Expression Omnibus (GEO) database (GSE76297, GSE32879, GSE26566, GSE31370, and GSE45001) and The Cancer Genome Atlas (TCGA) database. The Least absolute shrinkage and selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…As expected, Oil Red O staining showed that HepG2 cells treated with OA exhibited elevated intracellular lipid storage compared to the control cells ( Figure 5A). Consistent with previous report (25), OA reduced the expression of phosphatase and tensin homolog (PTEN) ( Figure 5B), a vital tumor suppressor gene in hepatocellular carcinoma. Importantly, OA markedly stimulated HMMR expression at the transcriptional and translational levels.…”
Section: Oleate Acid Elevates the Expression Of Hmmr Via Cebpαsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, Oil Red O staining showed that HepG2 cells treated with OA exhibited elevated intracellular lipid storage compared to the control cells ( Figure 5A). Consistent with previous report (25), OA reduced the expression of phosphatase and tensin homolog (PTEN) ( Figure 5B), a vital tumor suppressor gene in hepatocellular carcinoma. Importantly, OA markedly stimulated HMMR expression at the transcriptional and translational levels.…”
Section: Oleate Acid Elevates the Expression Of Hmmr Via Cebpαsupporting
confidence: 92%
“…Functional and pathway enrichment analyses were performed for DEGs using the clusterProfiler R package [25], including Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses [26]. GO terms and KEGG pathways with an adj.…”
Section: Functional and Pathway Enrichment Analysismentioning
confidence: 99%
“…Considering that previous research has mainly focused on one or two types of immune cells and key genes, it may create a bias against the LUAD microenvironment. Finding multiple genes from the tumor microenvironment to build a gene signature can obtain a better accuracy of the prognostic potential ( Liu et al, 2019a ,b; Zhou et al, 2019 ; Bi et al, 2020 ; Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, IRGs expression may be an important predictor of prognosis and progression in CCA. Up to date, considerable efforts have been made to identify prognostic model based on differentially expressed genes, but the report on prognostic IRGs signature of CCA is lacking [33,34]. In our study, we identi ed a new prognostic IRGs signature by screening the differentially expressed genes, and established a dependable model to predict survival of CCA patients based on this immune signature.…”
Section: Discussionmentioning
confidence: 97%